«CHIMERAS OF GREEN SUMMER» BY VALERY SHEVCHUK: TECHNIQUE OF CREATION OF ARTISTIC WORLD OF STORY - Khorob, M. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article researches the artistic technique components (of plot and composition, poetical and symbolic, oneiric and coloristic) in one of the 1980-s short prose pieces of the outstanding contemporary writer, that motivate Valeriy Shevchuk’s mastery of story creation.